DEVELOPMENT OF ECOTOURISM BASED MARINE TOURISM IN NISA/KAMBING ISLAND BIMA CITY NTB - Adi Hidayat Argubi; Ruli Inayah Ramadhoan; Hendra Hendra; Gufran Gufran (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The problem of this research was how the potential for developing marine tourism-based ecotourism; as well as assessing the carrying capacity and community participation in Nisa/Kambing Island Bima City NTB. This research is a descriptive study with a qualitative approach with techniques of data collection: observation, structured interviews, literature study, and questionnaires. In The population of this research is the people of Tanjung Sub District, Rasanae Barat District, Bima City as well as visiting tourists. Meanwhile, data analysis used descriptive and statistical analysis to analyze trends in community perceptions regarding carrying capacity and participation. The results showed Nisa/Kambing Island if developed well, will become one of the mainstays of marine tourism based on ecotourism in Bima City. The island, which is located in the Bima bay area, is surrounded by a charming natural panorama of the sea calm sea waters and perfect for water sports activities (Banana Boat, Jet Sky, etc.), Vollley beaches, swimming, diving, snorkeling, boating around and others and supported by attractions fishermen, the way of life and culture of the local community as well as camping areas available for the traveler. Nisa/Kambing Island has a lot of positive support from the community and tourists because the development must also be felt by the community, both from a social perspective, community culture, especially in the economic sector of the surrounding community. SWOT analysis results indicate that Nisa/Kambing Island has the power to become the leading tourist destination of the City. Keywords: Marine, Tourism, Development